Infants See Illusory Motion in Static Figures. (August 2013) - Kanazawa, So; Kitaoka, Akiyoshi; Yamaguchi, Masami K
We investigated illusory motion perception in 6-to-8-month-old infants using a static figure which produces strong illusory motion. In experiment 1 we prepared a control figure, which was physically similar to the illusory motion figure but which did not produce illusory motion. We presented the illusory figure and the control figure side-by-side, and measured infants' looking time at the target illusory figure. Results showed that the infants' looking time at the illusory figure was significantly longer than that for the control. In experiment 2 we made another set of stimuli consisting of the same local pattern used in experiment 1, but which did not produce illusory motion. The results showed that no preferences were observed in experiment 2. These results suggest that 6-to-8-month-old infants perceive illusory motion in static figures.